Trial and error. A new approach to space-bounded learning - Ameur, Foued; Fischer, Paul; Höffgen, Klaus -U.; Meyer auf der Heide, Friedhelm (Acta Informatica)

An Experimental Comparison of 3D Display Modes - Volbracht, S.; Domik, Gitta; Shahrbabaki, K.; Fels, G. (Proceedings of IEEE Visualization)

A Comparative Study of Linear Feature Transformation Techniques for Automatic Speech Recognition - Eisele, Thomas; Haeb-Umbach, Reinhold; Langmann, Detlev (ICSLP , Philadelphia)
Although widely used, there are still open questions concerning which properties of linear discriminant analysis (LDA) account for its success in many speech recognition systems. In order to gain more insight into the nature of the transformation we compare LDA with mel-cepstral feature vectors with respect to the following criteria: decorrelation and ordering property; invariance under linear transforms; automatic learning of dynamical features; and data dependence of the transformation.

3d core-level shifts at - Schmidt, Wolf Gero; Käckell, P.; Bechstedt, F. (Surface Science)

Se-induced 3d core-level shifts of GaAs(110) - Käckell, Peter; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Applied Surface Science)

De Caro, Mario, “Galileo’s Mathematical Platonism”, in: Czermak (Hg.) 1993 [Zbl 0836.00022], 13–22 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Franchella, Miriam, “L.E.J. Brouwer: Toward Intuitionistic Logic”, Historia Mathematica 22 (1995), 304–322 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Casati, Roberto/Smith, Barry/White, Graham (Hgg.), Philosophy of the Cognitive Sciences. Proceedings of the 16th International Wittgenstein-Symposium, 15–22 August 1993, Kirchberg am Wechsel, Austria, Hölder-Pichler-Tempsky: Wien 1994 (= Schriftenreihe der Wittgenstein-Gesellschaft; 21) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Sicherheitserziehung - ein Thema für den Arbeitslehreunterricht. - Bigga, Regine (ARBEIT UND TECHNIK in der Schule)

Visual Modeling and 3D-Representation with a Complete Visual Programming Language --- A Case Study in Manufacturing - Geiger, Christian; Hunstock, R.; Lehrenfeld, Georg; Müller, Wolfgang; Quintanilla, J.; Tahedl, C.; Weber, A. (Proceedings of the 1996 IEEE Symposium on Visual Languages)
The main goal of the article is to evaluate the suitability of visual programming languages, i.e., Pictorial Janus (K. Kahn and V. Saraswat, 1990), for the modeling of complex systems and their control strategies. These systems can be seen as networks of communicating objects. Objects select strategies for suitable actions based on incoming messages. Our field of investigation is in computer integrated manufacturing considering the example of a car manufacturing cell. This color sorting assembly buffer (CSAB) schedules jobs in queues. The jobs represent car bodies scheduled in feeder lines for the enameling. Feeder lines collect raw bodies to blocks. Blocks are bodies which are to be enameled by the same color. This organization decreases the cost of expensive change-over-times when changing colors at the enamelling. Blocks of bodies are dislocated from the queue and enameled successively. Contradictory system goals, such as minimizing color changes and preserving the sequence of incoming jobs, have to be regarded by appropriate control strategies. Due to the complexity of this (NP complete) problem and to real time requirements for online control there are no optimal strategies on hand. Consequently, suitable heuristics have to be developed. Often they are designed applying a trial-and-error method. A modeling framework has to support the rapid prototyping of these systems as well as an expressive end user oriented representation. Both are essential requirements since end users need other visualization techniques than experienced designers due to their different knowledge and interests.
Keywords: Computer integrated manufacturing; Job shop scheduling; Processor scheduling; Computer languages; Control system synthesis; Computer aided manufacturing; Sorting; Assembly; Costs; Control systems

Space-Bounded Learning Algorithms - Ameur, Foued

Computergestützte Intervention bei Rechtschreibschwäche: Effekte eines kognitions- und lernpsychologisch orientierten Trainingsprogramms auf Morphembasis bei sehr schwachen Sonderschülern. - Walther, J.; Bigga, Regine; Bischof, H. (Sonderpädagogik)

Weak Sequential Composition in Process Algebras - Rensink, Arend; Wehrheim, Heike (CONCUR '94, Concurrency Theory, 5th International Conference, Uppsala, Sweden, August 22-25, 1994, Proceedings)

Wozu Algebra der Logik? Ernst Schröders Suche nach einer universalen Theorie der Verknüpfungen - Peckhaus, Volker (Modern Logic)
Abstract: Historia Mathematica 22 (1995), #22.2.62 (I. Anellis). Rezensionen: Zbl. Math. 812.01012 (I. Grattan-Guinness); MR 95m:03002 (M. Guillaume).

Die Gleichstellung der Geschlechter im Lehrplan. Anregungen für Schule und Unterricht. - Bigga, Regine; Braun, F.; Hoffmann, L.

Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld Arbeitslehre - Tornieporth, G.; Bigga, Regine

Ergebnisse aus dem Projekt Mädchen & junge Frauen in der Arbeitswelt - Bigga, Regine (Erwerbsarbeit - Hausarbeit. Strukturwandel der Arbeit als Herausforderung an das Lernfeld der Arbeitslehre)

The Development of Ernst Schröder’s Attitude towards Logic [Abstract] - Peckhaus, Volker (XIXth International Congress of History of Science. 22–29 August 1993 Zaragoza (Spain). Book of Abstracts Symposia)

Leibniz’ ,Mathesis universalis‘ und die Mathematiker des 19. Jahrhunderts [Abstract] - Peckhaus, Volker (Fachsektion Geschichte der Mathematik der Deutschen Mathematiker-Vereinigung. Sektionstagung vom 22. bis 26. März 1993 in Wuppertal)

Forschungsergebnisse zur Geschlechterfrage - Konsequenzen für die Gestaltung von Unterricht sowie für die Aus- und Weiterbildung von Lehrkräften - Bigga, Regine (Lehrplanrevision in Schleswig-Holstein)

Die deutschsprachige Literatur Osteuropas und ihre Rezeption in der Bundesrepublik. Probleme und Chancen einer 'kleinen Literatur' - Eke, Norbert Otto (Deutsche Studien 29)
Auch erschienen in: Neue Zeitung [Budapest], Nr 28 vom 14.7.1990, S. 6-7, und Nr 29 vom 21.7.1990, S. 8-9, sowie Neue Literatur [Bukarest], H. 5-6/1990/91, S. 22-42

Berufsorientierung für Mädchen zwischen ,,typisch weiblichen" und ,,typisch männlichen" Berufen. - Bigga, Regine (Arbeitslehre und Polytechnik: Annäherung und Wandel. Beiträge zur technisch-ökonomischen Allgemeinbildung im vereinten Deutschland.)

Berufswahlverhalten und Lebensplanung von Mädchen. Ein Thema für die Schule und eine Aufgabe für die Gewerkschaften. - Bigga, Regine (Gewerkschaftliche Bildungspolitik)

Sexismus am Arbeitsplatz - Ein Tabuthema der Arbeitslehre. - Bigga, Regine (awt-info)

Friedhof als Quelle historischen Arbeitens. Der Eichhof Friedhof in Kiel/Kronshagen - Bigga, Regine; Colmorgen, Eckhard; Danker, Uwe; Dittrich, Irene (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

Erstellung einer Ton-Dia-Schau zum Einsatz im schulischen Unterricht für den Kreis Lippe zum 40. Jubiläum des Art. 3 Abs. 2 Grundgesetz “Männer und Frauen sind gleichberechtigt” - Schlegel-Matthies, Kirsten

Karl Eugen Müller (1865–1932) und seine Rolle in der Entwicklung der Algebra der Logik - Peckhaus, Volker (History and Philosophy of Logic)
Abstracts: The Philosopher's Index. Cumulative Edition 22 (1988), 509–510; Historical Abstracts 40A:4245. Rezensionen: Zbl. Math. 645.01019 (R. Murawski); MR 89e:01038 (Chris Brink).

Studium Arbeitslehre - Rückblick mit Ausblick - Bigga, Regine (Arbeitslehre / Polytechnik: Ein Beitrag zur Neuen Allgemeinbildung. Die Geschichte von Arbeit, Technik und Produktion im Unterricht)

Die Schleswig-Holsteinische Volkszeitung 1892 bis 1968 - Facetten aus ihrer Geschichte - Bigga, Regine; Danker, Uwe (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

Der VZ - Verlag in Photographien - Bigga, Regine; Danker, Uwe; Bruhn, Paul (Beirat für Geschichte der Arbeiterbewegung und Demokratie in Schleswig-Holstein)

Anschauliches Lernen im Museum. - Bigga, Regine (Allgemeinbildung und Arbeit, Technik, Wirtschaft - Innovationen in Curriculum und Schul-Praxis.)

Geschlechtsspezifische Arbeitsteilung und technische Innovation - Neue Technologien, Frauenerwerbsarbeit und historisch-genetisches Lernen über Arbeit und Technik. - Bigga, Regine; Oberliesen, R. (Neue Technologien und technisch-ökonomische Bildung.)